Effectiveness of Village Government Apparatus Performance in Village Fund Management (A Study in Sirenja District, Donggala Regency) - Yunus, Yunus; Gani, Juli Andi; Mardiyono, Mardiyono; Saleh, Chaerul (Sekolah Pascasarjana Universitas Brawijaya, 2023)
This study aims to analyze and determine the effectiveness of the performance of village government officials in managing village funds (a study in Sirenja District, Donggala District, researchers analyzed through performance effectiveness with indicators of work skills, improved achievement, ability to adapt, and able to deal with changes, the type of research conducted through descriptive qualitative approach the results of the study show the effectiveness of the performance of village government officials in management and villages in work skills is strongly influenced by the level of education, work experience and training, improvement in work performance based on the ability to make village maps, Season Calendar and Institutional diagrams, and the ability to Adaptation is seen from a more calm, flexible attitude, and mastering the field of work while being able to deal with changes is shown in the ability to change regulations and changes in weather, climate, air temperature. Keywords: performance effectiveness, village government apparatus, managing village funds